Las columnas de autor: Retórica y... ¿Diálogo? Caso práctico: La presencia del “otro” en el columnismo de Rosa Montero - García Álvarez, María Felicidad (Estudios sobre el Mensaje Periodístico, 2007)
The personal column or author’s column has been in the last years analyzed as a rhetoric text. However, most of the studies have limited the rhetoric composition to the presence of the ethos and the narrator as configurative elements of the column. In this article we intend to highlight the presence of the other in the columns, of an interlocutor whom the “I” establish an intern dialogue to confirm, discuss or debate his opinions and ideas, giving finally a stronger rhetoric force to the column. This article is a new perspective for the study of the column as a dialogical text.